ANALYSIS OF TAX BURDEN AND COMPANY SIZE AS DETERMINANTS OF TRANSFER PRICING DECISIONS - Firdaus, Rayhan; Rachmawati, Rima (Kajian Akuntansi, 2024)
Multinational companies often use transfer pricing to reduce their tax burden. This study examines the effect of tax burden and company size on the decision to engage in transfer pricing among manufacturing companies listed on the Indonesia Stock Exchange from 2018 to 2021. The study uses secondary data from financial reports with a multiple linear regression method. The results show that tax burden and company size influence transfer pricing. The larger the tax burden, the higher the tendency for companies to use transfer pricing to reduce taxes. Similarly, larger companies have more opportunities to engage in transfer pricing. The implications of this research support improvements in tax policies and stricter corporate governance to prevent the misuse of transfer pricing.   Keywords          : Company Size, Manufacturing Companies, Tax Burden, Transfer Pricing